Cariprazine Use in Early Psychosis: Three Case Reports - Coentre, Ricardo; Saraiva, Rodrigo; Sereijo, Carolina; Levy, Pedro (Frontiers in Psychiatry, 2021)
Objective: Cariprazine is a new atypical antipsychotic approved for the acute and maintenance treatment of schizophrenia (FDA, 2015; EMA, 2017) and for the treatment of manic or mixed episodes associated with bipolar I disorder (FDA, 2015). Recently, cariprazine also got extended FDA-approval for the treatment of depressive episodes in adults with bipolar I disorder (FDA, 2019). The use of low doses of atypical antipsychotics is an essential component of early intervention in psychosis. For its particular performance and tolerability, cariprazine is becoming an important option for the treatment of first-episode psychosis. Method: Three patients experiencing first-episode psychosis (FEP) were successfully treated with cariprazine. Two patients were in their first months of the disease, and the third patient was in his third year of FEP. Results: The three patients had a diagnosis of non-affective FEP, which includes schizophrenia, delusional disorder, and schizoaffective disorder. One of them was in their third year of FEP with a predominance of negative symptoms at this stage of the disorder. All the patients were treated with cariprazine with a target dose of 3–4.5mg/day. The three patients showed improvements in their psychosis, including a decrease in negative symptoms. No significant side effects were reported. Conclusion: Our three case reports indicate that cariprazine is an atypical antipsychotic beneficial in the treatment of early psychosis. Treatment with low doses of cariprazine could be effective and tolerable in early psychosis. Future studies with longer follow-up of FEP patients are recommended to confirm these positive results of cariprazine in the early phases of psychosis.